Tribological Behaviour Of GreenCarbon Fibre Waste Reinforced Thermoplastic Composites Prepared Via Melt Mixing - Ab Maulod, Hairul Effendy; Mohamad, Noraiham; Shamsuri, Siti Rahmah; Ahsan, Qumrul; Mohd Abid, Mohd Asyadi ‘Azam; Zainal Abidin, Muhammad Zaimi; Abdollah, Mohd Fadzli (UTeM, 2018)
Recently, the use of carbon fiber waste is accepted as a wise approach to benefit the performance of the carbon fiber and considered as green effort for disposal management. This research is an effort to study the potential of recycled carbon fibers as reinforcement in polypropylene (PP) matrix especially for tribology application. The effects of fibers condition, fiber loading as well as chemical modifications on physical, mechanical and tribological properties of PP reinforced with recycled carbon fibers were studied. The composites were prepared via melt compounding using a Haake internal mixer at 180 ºC and rotor speed of 50 rpm for 10 minutes. This research is divided into three different studies; 1) effect of recycled carbon fibers condition (with or without uncured resins) on the physical and tensile properties at different carbon fiber (CF) loading of 0, 3, 5, 10, 13, 15 wt%, 2) effect of chemical modification using 3 and 5 wt% maleic anhydride (MA) on the tensile properties and 3) wear characteristics of recycled carbon fiber reinforced polypropylene composites at CF loading of 0, 0.5, 1.0, 3.0, 5.0, 7.0, 10.0, 13.0, 15.0, 20.0 wt%. In Study 1, the uncured resins on carbon fibers had proven to improve the interaction between reinforcement and matrix which manifested by increment in physical and mechanical properties with the optimum at 3 wt% fiber loading. In Study 2, the recycled carbon fibers were first pulverized into finer fibers before undergone oxidation in nitric acid and treatment with maleic anhydride. The treatment was observed to improve the physical and mechanical properties of the composites at low MA content of 3 wt% and proven to increase interaction at limited loading of fibers for only up to 1 wt%. The properties were supported by morphological analysis on the fracture surfaces observed by using Scanning Electron Microscopy and chemical analysis using Fourier Transform Infrared Spectroscopy. In Study 3, the composites with low carbon fiber loading of up to 3 wt% imposed higher resistance to dry sliding friction. In contrast, the increment of fiber loading at 5 wt% to 20 wt%, decreased the wear rate of the composites due to the formation of patchfilm and transfer film which accelerated with the MA treatment. The wear mechanism of the composites was for different fiber loading was proposed from morphological observation. As the conclusions, the composites showed promising self- lubricating properties with significant physical and mechanical properties.